2011
DOI: 10.1111/j.1440-1754.2011.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute suppurative thyroiditis in young children

Abstract: We report two children with acute suppurative thyroiditis (AST). They presented with typical features of AST, which include fever, painful goiter and biochemical euthyroidism. An anatomical defect predisposed to thyroid infection, pyriform sinus fistula, was identified in one patient. Both patients responded well to surgical pus drainage and antibiotic treatment. Anatomical defects must be sought in all children with AST to perform specific surgical treatment and prevent recurrent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This in turn affected her presentation to our care and masked the picture as she was non-toxic and not exhibiting much of symptoms, although her infection extended up to the mediastinum. This has been reported before by Wongphyat et al [ 15 ], but unlike our case, their patients later developed more signs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This in turn affected her presentation to our care and masked the picture as she was non-toxic and not exhibiting much of symptoms, although her infection extended up to the mediastinum. This has been reported before by Wongphyat et al [ 15 ], but unlike our case, their patients later developed more signs.…”
Section: Discussionsupporting
confidence: 80%
“…Ultrasound is a reasonable first-line imaging study in the emergency department as it can detect early signs before progression to abscess formation. Based on findings on ultrasound, a decision can be made to proceed to the next step in imaging such as a CT scan [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, Mycobacteria , Aspergillus , Coccidioidesimmitis , Cryptococcus neoformans , Histoplasma capsulatum , Candida , Treponema pallidum , and Echinococcus have been identified. As much as 30% of suppurative thyroiditis are polymicrobial infection1,3,4).…”
Section: Discussionmentioning
confidence: 99%
“…A large review of 526 cases published by Nicoucar et al [1] showed that AST is the most common presentation of pyriform sinus fistula, especially in children [2]. According to these authors, the latency of recurring episodes occurring after performing a thyroidectomy may lead to a delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%